Hard carbon sodium battery negative electrode material taking peanut shells as raw materials and preparation method thereof

By using the mixture of disodium ethylenediaminetetraacetic acid solution and peanut shell powder and calcining treatment under nitrogen atmosphere when preparing hard carbon sodium electro-negative material, the problems of low charge and discharge capacity and low initial Coulomb efficiency are solved, and higher charge and discharge capacity and more stable cycle performance are achieved.

CN119833630AActive Publication Date: 2025-04-15CHANGSHU INSTITUTE OF TECHNOLOGY

Patent Information

Application Number
CN202510310097.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-17
Publication Date
2025-04-15
Estimated Expiration
2045-03-17

AI Technical Summary

Technical Problem

In the prior art, hard carbon materials are prepared using peanut shells as raw materials for the negative electrode of sodium ion batteries. The charging and discharge capacity is low and the initial Coulomb efficiency is low. This is mainly due to the excessive specific surface area of ​​the product and excessive adsorption of sodium ions, which reduces the charge and discharge efficiency.

Method used

A hard carbon sodium electronegative material with a graphitized area with a scale of 0.6 to 3 nm was prepared by mixing the disodium ethylenediaminetetraacetic acid solution with a preoxidized peanut shell powder and calcined and carbonized under a nitrogen atmosphere.

Benefits of technology

The charging and discharging capacity and initial Coulomb efficiency of hard carbon materials are improved, ensuring that the charging specific capacity of the first round of the material at a charge and discharge rate of 0.1C is between 264 and 318mAh·g-1, and the Coulomb efficiency of the first round is between 74% and 84%, and the capacity retention rate reaches 84% ​​and 91% after 50 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833630A_ABST
    Figure CN119833630A_ABST
Patent Text Reader

Abstract

The invention discloses a hard carbon sodium battery negative electrode material taking peanut shells as a raw material, which is micron-sized particles of mixed nano-particles containing C, O, Na and N. After the material is subjected to ultrasonic dispersion, holes are wrapped by graphitization-like areas with the size range of 0.6-3 nm to form disordered accumulation, and the average graphite layer spacing is 3.6-4.0. The preparation method comprises the following steps: heating and pre-oxidizing the peanut shells in an air atmosphere, grinding or crushing the peanut shells into powder, adding a disodium ethylene diamine tetraacetate solution, uniformly stirring, and drying; and calcining and carbonizing the dried mixture in a nitrogen atmosphere, and cooling to obtain the hard carbon sodium battery negative electrode material taking the peanut shells as the raw material. When the obtained hard carbon material serves as a sodium ion battery negative electrode and is charged and discharged at 0.1 C, the initial charging specific capacity can reach 274-318 mAh.g <-1 >, the first-circle coulombic efficiency reaches 74%-84%, and the problems that a hard carbon sodium battery negative electrode material is low in capacity and low in initial coulombic efficiency are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a hard carbon sodium negative electrode material and a preparation method thereof, belonging to the technical field of electrode materials. Background Art

[0002] Peanut shells, as waste from the edible oil industry, are rich in lignin and can be used to prepare hard carbon materials. However, the charge and discharge capacity of the carbon material obtained by directly treating peanut shells at high temperature is not high. In the scheme of the prior art, the peanut shells are soaked in concentrated phosphoric acid for a long time before calcination to increase the active sites, hoping to improve the charge and discharge capacity, but this results in a low initial coulomb efficiency of the final hard carbon product of only 68%. This may be because the soaking process in phosphoric acid gives the product hard carbon a larger specific surface area. The strong adsorption of sodium ions on these surfaces will reduce the first cycle coulomb efficiency of the material's charge and discharge, thereby dragging down the performance of the positive electrode material, which will make the long-term charge and discharge stability of the full battery poor.

[0003] Therefore, when using peanut shells as raw materials to prepare hard carbon materials for use as negative electrodes in sodium-ion batteries, it is necessary to solve the problem of low capacity. While increasing active sites to improve capacity, it is also necessary to prevent the generation of a large specific surface area to avoid reducing the initial coulombic efficiency of the material. Summary of the invention

[0004] In response to the above technical needs, the present invention provides a method for preparing a hard carbon sodium negative electrode material using peanut shells as raw materials, and provides a hard carbon sodium negative electrode material using peanut shells as raw materials prepared by the preparation method, so as to solve the problem of low capacity and low initial coulombic efficiency of the material.

[0005] The technical solution of the present invention is: a hard carbon sodium negative electrode material using peanut shells as raw materials, wherein the hard carbon sodium negative electrode material using peanut shells as raw materials is micron-sized particles of mixed nanoparticles containing C, O, Na, and N elements, and after ultrasonic dispersion, the hard carbon sodium negative electrode material using peanut shells as raw materials has a graphitized region with a scale range of 0.6 to 3 nm that wraps the pores to form a chaotic stack, and has an average graphite layer spacing of 3.6 to 4.0 Å.

[0006] Another technical solution of the present invention is: a method for preparing a hard carbon sodium negative electrode material using peanut shells as raw materials, comprising the steps of: S1, heating and pre-oxidizing the peanut shells under air atmosphere conditions; S2, grinding or crushing the pre-oxidized peanut shells into powder, adding disodium ethylenediaminetetraacetic acid solution, stirring evenly and then drying; S3, placing the mixture dried in step S2 under a nitrogen atmosphere for calcination and carbonization, and obtaining a hard carbon sodium negative electrode material using peanut shells as raw materials after cooling.

[0007] Another technical solution of the present invention is: a method for preparing a hard carbon sodium negative electrode material using peanut shells as raw materials, comprising the steps of: S0, placing the peanut shells in a hydrochloric acid solution and heating them, then separating the solid matter from the solution, washing and drying them; S1, placing the peanut shells dried in step S0 in an air atmosphere for heating and pre-oxidation; S2, grinding or crushing the pre-oxidized peanut shells into powder, adding a disodium ethylenediaminetetraacetic acid solution, stirring evenly and then drying; S3, placing the mixture dried in step S2 in a nitrogen atmosphere for calcination and carbonization, and obtaining a hard carbon sodium negative electrode material using peanut shells as raw materials after cooling.

[0008] In the technical solution of the method for preparing hard carbon sodium negative electrode material using peanut shell as raw material, further, in the step S1, the pre-oxidation temperature is 200-300°C.

[0009] Furthermore, in step S2, the mass ratio of disodium ethylenediaminetetraacetate in the disodium ethylenediaminetetraacetate solution to the mass ratio of the powdered peanut shells is 2% to 8%.

[0010] Furthermore, in the step S3, the temperature of the calcination and carbonization in the nitrogen atmosphere is 1200-1400° C., and the calcination and carbonization treatment time is 0.5-5 h.

[0011] Furthermore, in the step S0, the concentration of the hydrochloric acid is 0.5 to 2 mol / L, the heating temperature is 60 to 150° C., and the heating time is 0.5 to 5 h.

[0012] The advantages of the present invention compared with the prior art are: (1) The disodium ethylenediaminetetraacetic acid added during the preparation process contains nitrogen, oxygen, and sodium. The oxygen element may increase the disorder of the final hard carbon material and provide active sites; the nitrogen element not only provides active sites, but also may improve the conductivity of the material; the sodium element will be reduced to elemental sodium in a reducing atmosphere and evaporated at high temperature. This process may produce sodium ion channels, which facilitates the subsequent charging and discharging of the sodium negative electrode as a sodium electrode, and the sodium ions are reduced and enter the interior of the material. These factors make the product hard carbon have a higher charge and discharge capacity than the hard carbon material produced by directly calcining peanut shells.

[0013] (2) The above process of adding disodium ethylenediaminetetraacetic acid does not produce wastewater, and the addition ratio is very low, so it has little impact on the cost of the product hard carbon.

[0014] (3) Adding disodium ethylenediaminetetraacetic acid and then calcining peanut shells will not increase the specific surface area of ​​the product hard carbon, thereby avoiding the decrease in the first-cycle coulomb efficiency of the product when used as the negative electrode of a sodium ion battery for charging and discharging.

[0015] (4) The pre-treatment with hydrochloric acid can partially hydrolyze the lignin in the peanut shell, shortening and reducing its structural chain segments, which helps to fully contact with the subsequently added disodium ethylenediaminetetraacetic acid at the microscopic level, thereby enabling the product hard carbon to further provide a higher charge and discharge specific capacity. In addition, this hydrochloric acid treatment step does not reduce the first cycle coulombic efficiency of the product hard carbon.

[0016] (5) The sodium ion half-cell assembled from the hard carbon sodium negative electrode material prepared by the present invention using peanut shell as raw material has a high conductivity at 0.1C (1C = 300mAg -1 ) can provide 264~318mAh·g -1 The initial charge specific capacity is 100%, the first cycle coulomb efficiency is between 74% and 84%, and the capacity retention rate after 50 stable cycles is between 84% and 91%. These characteristics make the material suitable for practical energy storage applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is the powder X-ray diffraction (XRD) spectrum of the hard carbon sodium negative electrode material using peanut shell as raw material obtained in Example 1.

[0018] Figure 2 This is the powder X-ray diffraction (XRD) spectrum of the hard carbon sodium negative electrode material using peanut shell as raw material obtained in Example 4.

[0019] Figure 3 This is the powder X-ray diffraction (XRD) spectrum of the hard carbon sodium negative electrode material using peanut shell as raw material obtained in Example 5.

[0020] Figure 4 This is a scanning electron microscope (SEM) image of the hard carbon sodium negative electrode material using peanut shell as raw material obtained in Example 1.

[0021] Figure 5 This is a scanning electron microscope (SEM) image of the hard carbon sodium negative electrode material obtained using peanut shell as raw material in Example 4.

[0022] Figure 6 This is a scanning electron microscope (SEM) image of the hard carbon sodium negative electrode material using peanut shell as raw material obtained in Example 5.

[0023] Figure 7 The transmission electron microscope (TEM) image and element distribution map of the hard carbon sodium negative electrode material using peanut shell as raw material obtained in Example 1. The sample powder of Example 1 was firstly ultrasonically treated in anhydrous ethanol, then dispersed on the surface of a copper mesh and then photographed by transmission electron microscope.

[0024] Figure 8The transmission electron microscope (TEM) image and element distribution map of the hard carbon sodium negative electrode material using peanut shell as raw material obtained in Example 4. The sample powder of Example 4 was firstly ultrasonically treated in anhydrous ethanol, then dispersed on the surface of a copper mesh and then photographed by transmission electron microscope.

[0025] Fig. 9 The transmission electron microscope (TEM) image and element distribution map of the hard carbon sodium negative electrode material using peanut shell as raw material obtained in Example 5. The sample powder of Example 5 was firstly ultrasonically treated in anhydrous ethanol, then dispersed on the surface of a copper mesh and then photographed by transmission electron microscope.

[0026] Fig.10 This is a diagram of the variable rate cycling effect after the hard carbon sodium negative electrode material using peanut shells as raw materials obtained in Example 1 is assembled with sodium sheets into a sodium ion half-cell.

[0027] Fig.11 This is a diagram of the variable rate cycling effect after the hard carbon sodium negative electrode material using peanut shells as raw materials obtained in Example 4 is assembled with sodium sheets into a sodium ion half-cell.

[0028] Fig.12 This is a diagram of the variable rate cycling effect after the hard carbon sodium negative electrode material using peanut shells as raw materials obtained in Example 5 is assembled with sodium sheets into a sodium ion half-cell.

[0029] Fig.13 This is a diagram of the variable rate cycling effect after the hard carbon material obtained by directly calcining peanut shells and sodium sheets are assembled into a sodium ion half-cell in the comparative example.

[0030] Fig.14 It is a comparison chart of the long cycle effect of the sodium ion half-cell of Examples 1 to 9 and the comparative example at a rate of 0.1C. DETAILED DESCRIPTION

[0031] The present invention will be further described below in conjunction with the embodiments, but are not intended to limit the present invention.

[0032] Embodiment 1:

[0033] (1) The peanut shells are placed in an air atmosphere and heated for pre-oxidation at a temperature of 250°C; (2) grinding or crushing the pre-oxidized peanut shells into powder, dissolving 5% by weight of disodium ethylenediaminetetraacetate in distilled water to form a clear solution, adding the solution to the peanut shell powder and stirring evenly, and drying the mixed system; (3) placing a mixture of dried peanut shell powder and disodium ethylenediaminetetraacetate under a N2 atmosphere, heating it to 1300°C and maintaining the temperature for 2 hours, and then cooling it to obtain the hard carbon sodium negative electrode material using peanut shell as raw material. The material can provide 274 mAh·g at 0.1°C. -1The first cycle charge specific capacity, the first cycle coulomb efficiency is 77%, and the capacity after 50 cycles at 0.1C is 231mAh g -1 , the capacity retention rate is 84%.

[0034] Embodiment 2:

[0035] (1) The peanut shells are placed in an air atmosphere and heated for pre-oxidation at a temperature of 200°C; (2) grinding or crushing the pre-oxidized peanut shells into powder, dissolving 2% by weight of disodium ethylenediaminetetraacetate in distilled water to form a clear solution, adding the solution to the peanut shell powder and stirring evenly, and drying the mixed system; (3) The mixture of dried peanut shell powder and disodium ethylenediaminetetraacetate was placed in a N2 atmosphere, heated to 1200°C and maintained at this temperature for 5 hours, and then cooled to obtain the hard carbon sodium negative electrode material using peanut shell as raw material. The material can provide 264 mAh·g at 0.1C. -1 The first cycle charge specific capacity, the first cycle coulomb efficiency is 75%, and the capacity after 50 cycles at 0.1C is 226mAh g -1 , the capacity retention rate is 86%.

[0036] Embodiment 3:

[0037] (1) The peanut shells are placed in an air atmosphere and heated for pre-oxidation at a temperature of 300°C; (2) grinding or crushing the pre-oxidized peanut shells into powder, dissolving 8% by weight of disodium ethylenediaminetetraacetate in distilled water to form a clear solution, adding the solution to the peanut shell powder and stirring evenly, and drying the mixed system; (3) Place the mixture of dried peanut shell powder and disodium ethylenediaminetetraacetate in a N2 atmosphere, heat it to 1400°C and maintain the temperature for 0.5 hours, and then cool it to obtain the hard carbon sodium negative electrode material using peanut shell as raw material. The material can provide 271mAh·g at 0.1C. -1 The first cycle charge specific capacity is 75%, and the capacity is 238 mAh g after 50 cycles at 0.1 C. -1 , the capacity retention rate is 88%.

[0038] Embodiment 4:

[0039] (1) Put peanut shells into an acid-resistant container, add 1 mol / L HCl solution to submerge the peanut shells, seal the container and heat at 100°C for 2 hours, separate the solid matter after cooling, wash and dry; (2) heating the dried peanut shells in an air atmosphere for pre-oxidation at a temperature of 250° C.; (3) Grinding or crushing the pre-oxidized peanut shells into powder, dissolving 5% by mass of disodium ethylenediaminetetraacetate in distilled water to form a clear solution, adding the solution to the peanut shell powder, stirring evenly, and drying the mixed system; (4) Place the mixture of dried peanut shell powder and disodium ethylenediaminetetraacetate in a N2 atmosphere, heat it to 1300°C and maintain the temperature for 2 hours, then cool it to obtain the hard carbon sodium negative electrode material using peanut shell as raw material. The material can provide 296 mAh·g at 0.1C. -1 The first cycle charge specific capacity is 84%, and the first cycle coulomb efficiency is 84%. After 50 cycles at 0.1C, the capacity is 255mAh g -1 , the capacity retention rate is 86%.

[0040] Embodiment 5:

[0041] (1) Put peanut shells into an acid-resistant container, add 1 mol / L HCl solution to immerse the peanut shells, seal the container and heat at 80°C for 2 hours, separate the solid matter after cooling, wash and dry; (2) heating the dried peanut shells in an air atmosphere for pre-oxidation at a temperature of 250° C.; (3) grinding or crushing the pre-oxidized peanut shells into powder, dissolving 5% by mass of disodium ethylenediaminetetraacetate in distilled water to form a clear solution, adding the solution to the peanut shell powder and stirring evenly, and drying the mixed system; (4) Place the mixture of dried peanut shell powder and disodium ethylenediaminetetraacetate under N2 atmosphere, heat to 1300°C and maintain the temperature for 2 hours, then cool to obtain the hard carbon sodium negative electrode material using peanut shell as raw material. The material can provide 318 mAh·g at 0.1C. -1 The first cycle charge specific capacity, the first cycle coulomb efficiency is 74%, and the capacity after 50 cycles at 0.1C is 287mAh·g -1 , the capacity retention rate is 90%.

[0042] Embodiment 6:

[0043] (1) Put peanut shells into an acid-resistant container, add 0.5 mol / L HCl solution to submerge the peanut shells, seal the container and heat at 60°C for 5 hours, separate the solid matter after cooling, wash and dry; (2) heating the dried peanut shells in an air atmosphere for pre-oxidation at a temperature of 300° C.; (3) Grinding or crushing the pre-oxidized peanut shells into powder, dissolving 2% by weight of disodium ethylenediaminetetraacetate in distilled water to form a clear solution, adding the solution to the peanut shell powder and stirring evenly, and drying the mixed system; (4) Place the mixture of dried peanut shell powder and disodium ethylenediaminetetraacetate in a N2 atmosphere, heat it to 1300°C and maintain the temperature for 2 hours, then cool it to obtain the hard carbon sodium negative electrode material using peanut shell as raw material. The material can provide 285 mAh·g at 0.1C. -1 The first cycle charge specific capacity, the first cycle coulomb efficiency is 78%, and the capacity after 50 cycles at 0.1C is 258mAh g -1 , the capacity retention rate is 91%.

[0044] Embodiment 7:

[0045] (1) Add peanut shells into an acid-resistant container, add 2 mol / L HCl solution to submerge the peanut shells, seal the container and heat at 150°C for 0.5 hour, separate the solid matter after cooling, wash and dry; (2) heating the dried peanut shells in an air atmosphere for pre-oxidation at a temperature of 250° C.; (3) Grinding or crushing the pre-oxidized peanut shells into powder, dissolving 4% by weight of disodium ethylenediaminetetraacetate in distilled water to form a clear solution, adding the solution to the peanut shell powder and stirring evenly, and drying the mixed system; (4) Place the mixture of dried peanut shell powder and disodium ethylenediaminetetraacetate in a N2 atmosphere, heat it to 1300°C and maintain the temperature for 2 hours, then cool it to obtain the hard carbon sodium negative electrode material using peanut shell as raw material. The material can provide 274 mAh·g at 0.1C. -1 The first cycle charge specific capacity, the first cycle coulomb efficiency is 80%, and the capacity after 50 cycles at 0.1C is 237mAh·g -1 , the capacity retention rate is 86%.

[0046] Embodiment 8:

[0047] (1) Put peanut shells into an acid-resistant container, add 1 mol / L HCl solution to submerge the peanut shells, seal the container and heat at 100°C for 2 hours, separate the solid matter after cooling, wash and dry; (2) heating the dried peanut shells in an air atmosphere for pre-oxidation at a temperature of 200° C.; (3) Grinding or crushing the dried pre-oxidized peanut shells into powder, dissolving 8% by mass of disodium ethylenediaminetetraacetate in distilled water to form a clear solution, adding the solution to the peanut shell powder, stirring evenly, and drying the mixed system; (4) placing a mixture of peanut shell powder and disodium ethylenediaminetetraacetate under a N2 atmosphere, heating it to 1200°C and maintaining the temperature for 5 hours, and then cooling it to obtain the hard carbon sodium negative electrode material using peanut shell as raw material. The material can provide 282 mAh·g at 0.1C. -1 The first cycle charge specific capacity, the first cycle coulomb efficiency is 77%, and the capacity after 50 cycles at 0.1C is 239mAh g -1 , the capacity retention rate is 85%.

[0048] Embodiment 9:

[0049] (1) Put peanut shells into an acid-resistant container, add 1 mol / L HCl solution to submerge the peanut shells, seal the container and heat at 100°C for 2 hours, separate the solid matter after cooling, wash and dry; (2) heating the dried peanut shells in an air atmosphere for pre-oxidation at a temperature of 250° C.; (3) grinding or crushing the pre-oxidized peanut shells into powder, dissolving 5% by mass of disodium ethylenediaminetetraacetate in distilled water to form a clear solution, adding the solution to the peanut shell powder and stirring evenly, and drying the mixed system; (4) Place the mixture of dried peanut shell powder and disodium ethylenediaminetetraacetate in a N2 atmosphere, heat it to 1400°C and maintain the temperature for 0.5 hours, and then cool it to obtain the hard carbon sodium negative electrode material using peanut shell as raw material. The material can provide 278 mAh·g at 0.1C. -1 The first cycle charge specific capacity, the first cycle coulomb efficiency is 77%, and the capacity after 50 cycles at 0.1C is 242mAh g -1 , the capacity retention rate is 87%.

[0050] Comparative Example: (1) The peanut shells are placed in an air atmosphere and heated for pre-oxidation at a temperature of 250°C; (2) The pre-oxidized peanut shells were ground or crushed into powder, placed in a N2 atmosphere, heated to 1300°C and maintained at this temperature for 2 hours, and then cooled to obtain a hard carbon material using peanut shells as a raw material. This material can provide 256 mAh·g -1 The first cycle charge specific capacity, the first cycle coulomb efficiency is 72%, and the capacity after 50 cycles is 219 mAh g -1 , the capacity retention rate is 86%.

[0051] In order to verify the structural characteristics and performance of the product obtained by the method of the present invention, the structure and performance of the obtained material are characterized.

[0052] from Figure 1 It can be seen that in the XRD spectrum of the hard carbon sodium negative electrode material using peanut shell as raw material prepared in Example 1, 2 θ There are two broad peaks at angles of 24.1° and 43.7°. The positions of the diffraction peaks are similar to the diffraction peaks of the (002) and (100) crystal planes of graphite (2 θ The angle positions are 26.5° and 42.8° respectively), but the diffraction peak angle of 24.1° of the sample in Example 1 is lower, corresponding to a wider average interlayer spacing of the (002) crystal plane, 3.69 Å, while the interlayer spacing of the normal graphite (002) crystal plane is 3.35 Å. The wider interlayer spacing is conducive to the embedding of sodium ions into the graphitized interlayer structure and internal pores, providing higher charge and discharge capacity. Both diffraction peaks of the XRD spectrum are broad peaks, indicating that the sample in Example 1 has a chaotic structure, which can be considered to be formed by the loose stacking of small-scale graphitized areas.

[0053] from Figure 2 It can be seen that in the XRD spectrum of the hard carbon sodium negative electrode material using peanut shell as raw material prepared in Example 4, 2 θ There are two broad peaks at angles of 23.2° and 43.7°. The diffraction peak at 23.2° corresponds to an average interlayer spacing of 3.83 Å on the (002) crystal plane. In addition, the two diffraction peaks are also broad peaks, which can also be inferred that the sample in Example 4 also has a chaotic structure, which is formed by the loose stacking of small-scale graphitized regions.

[0054] from Figure 3 It can be seen that in the XRD spectrum of the hard carbon sodium negative electrode material using peanut shell as raw material prepared in Example 5, 2 θ There are two broad peaks at angles of 22.6° and 43.7°. The diffraction peak at 22.6° corresponds to an average interlayer spacing of 3.93 Å on the (002) crystal plane. In addition, the two diffraction peaks are also broad peaks, which can also be inferred that the sample in Example 5 also has a chaotic structure, which is formed by the loose stacking of small-scale graphitized regions.

[0055] from Figure 4 From the scanning electron microscope (SEM) image, it can be seen that the product prepared in Example 1 is mostly irregular micron-sized granular material mixed with a small amount of nano-sized particles.

[0056] from Figure 5 It can be seen from the scanning electron microscope image that the product prepared in Example 4 is mostly irregular micron-sized granular material mixed with a small amount of nano-sized particles.

[0057] from Figure 6It can be seen from the scanning electron microscope image that the product prepared in Example 5 is mostly irregular micron-sized granular material mixed with a small amount of nano-sized particles.

[0058] Figure 7 (a) and (b) are transmission electron microscope images of different magnifications of the hard carbon sodium negative electrode material using peanut shell as raw material obtained in Example 1. Figure 7 It can be seen from the transmission electron microscope (TEM) that after ultrasonic dispersion, the chaotic accumulation formed by the graphitized areas with a diameter of about 1 to 3 nm wrapped around the pores can be observed on the lamellar structure of the sample of Example 1, as shown in FIG. Figure 7 As shown in (b), the white dot areas in the figure have a large proportion of transmitted light, indicating that these areas have low quality thickness and exist porous structures. Figure 7 The randomly selected sample particles of Example 1 shown in (c) show uniformly distributed C, O, Na, and N elements, which are shown in sequence in Figure 7 Element distribution diagrams in (d), (e), (f), and (g).

[0059] Figure 8 (a) and (b) are transmission electron microscope images of different magnifications of the hard carbon sodium negative electrode material using peanut shell as raw material obtained in Example 4. Figure 8 It can be seen from the transmission electron microscope (TEM) that after ultrasonic dispersion, the chaotic accumulation formed by the graphitized regions with a diameter of about 0.6-2.5 nm wrapped around the pores can be observed on the lamellar structure of the sample of Example 4, as shown in FIG. Figure 8 As shown in (b). Figure 8 The randomly selected sample particles of Example 4 shown in (c) show uniformly distributed C, O, Na, and N elements, which are shown in sequence in Figure 8 Element distribution diagrams in (d), (e), (f), and (g).

[0060] Fig. 9 (a) and (b) are transmission electron microscope images of different magnifications of the hard carbon sodium negative electrode material using peanut shell as raw material obtained in Example 5. Fig. 9 It can be seen from the transmission electron microscope (TEM) that after ultrasonic dispersion, the chaotic accumulation formed by the graphitized areas with a diameter of about 0.6-2.5 nm wrapped around the pores can be observed on the lamellar structure of the sample of Example 5, as shown in FIG. Fig. 9 As shown in (b). Fig. 9 The randomly selected sample particles of Example 5 shown in (c) show uniformly distributed C, O, Na, and N elements, which are shown in sequence. Fig. 9 Element distribution diagrams in (d), (e), (f), and (g).

[0061] from Fig.10It can be seen that the hard carbon sodium negative electrode material prepared in Example 1 using peanut shell as raw material is assembled into a half-cell, and the first cycle charging capacity is 274 mAh·g at a charge and discharge rate of 0.1C. -1 The first cycle coulomb efficiency is 77%. The material can be charged and discharged at a variable rate, with the highest rate being 5C. When the low rate (0.1C) is restored to charge and discharge, the charging capacity is restored to 245mAh·g -1 , slightly lower than the initial charge capacity. Except for the first cycle and when switching current density, the coulomb efficiency fluctuates, and in other cases the coulomb efficiency is close to 100%.

[0062] from Fig.11 It can be seen that the hard carbon sodium negative electrode material obtained in Example 4 using peanut shell as raw material is assembled into a half-cell, and the first cycle charging capacity reaches 296 mAh g at 0.1C. -1 The first cycle coulombic efficiency reaches 84%. The material can withstand high-rate charge and discharge of 5C, and after returning to a low rate (0.1C), the charging capacity can be restored to 275mAh·g -1 Except for the first cycle and when switching the magnification, the coulomb efficiency is close to 100% in other cases.

[0063] from Fig.12 It can be seen that the hard carbon sodium negative electrode material obtained in Example 5 using peanut shell as raw material is assembled into a half-cell, and the first cycle charging capacity reaches 318 mAh g at 0.1C. -1 The first cycle coulombic efficiency reaches 74%. The material can withstand high-rate charge and discharge of 5C, and after returning to a low rate (0.1C), the charging capacity can be restored to 303mAh·g -1 Except for the first cycle and when switching the magnification, the coulomb efficiency is close to 100% in other cases.

[0064] from Fig.13 It can be seen that the hard carbon material obtained by directly calcining peanut shells in the comparative example was assembled into a half-cell, and the first cycle charging capacity was 255 mAh g at 0.1 C. -1 The initial coulombic efficiency is 72%. When the sample is restored to 0.1C after high-rate charge and discharge, the charge capacity is 230mAh·g -1 .

[0065] from Fig.14 It can be seen that compared with the comparative example, Examples 1 to 3 (i.e., the peanut shell hard carbon material treated only by steps S1 to S3) have a higher charge capacity. After 50 cycles, the charge capacity retention rate is between 84% and 88%. On this basis, by adding the pre-treatment step of S0 hydrochloric acid, Examples 4 to 9 further improve the charge capacity of the material as a sodium negative electrode. After 50 cycles, the charge capacity retention rate is between 85% and 91%. In addition, the decrease in the charge capacity between the 10th and 11th cycles of all the examples and comparative examples shown in the figure is due to the insertion of Figures 10 to 13 The high rate charge and discharge of 0.2C to 5C shown in the figure is caused; if the influence of high rate charge and discharge is excluded, the capacity retention rate after 50 cycles can be further improved by about 2%. In addition, since all tests are performed with sodium sheets as counter electrodes, sodium dendrites are easily formed, which affects the test stability; therefore, it is speculated that the hard carbon material of the present invention, when applied to full batteries, will have further improvements in long-term charge and discharge stability and capacity retention rate.

Claims

1. A hard carbon sodium negative electrode material using peanut shell as raw material, characterized in that: The hard carbon sodium negative electrode material using peanut shell as raw material is micron-sized particles of mixed nanoparticles containing C, O, Na, and N elements. After ultrasonic dispersion, the hard carbon sodium negative electrode material using peanut shell as raw material has a graphitized region with a scale range of 0.6 to 3 nm that wraps the pores to form a chaotic stack, and has an average graphite layer spacing of 3.6 to 4.0 Å.

2. A method for preparing a hard carbon sodium negative electrode material using peanut shell as raw material as claimed in claim 1, characterized in that: The method comprises the following steps: S1, heating and pre-oxidizing peanut shells under air atmosphere; S2, grinding or crushing the pre-oxidized peanut shells into powder, adding disodium ethylenediaminetetraacetic acid solution, stirring evenly and drying; S3, calcining and carbonizing the mixture after drying in step S2 under nitrogen atmosphere, and obtaining hard carbon sodium negative electrode material with peanut shells as raw materials after cooling.

3. The method for preparing a hard carbon sodium negative electrode material using peanut shell as raw material according to claim 2, characterized in that: In the step S1, the pre-oxidation temperature is 200-300°C.

4. The method for preparing a hard carbon sodium negative electrode material using peanut shell as raw material according to claim 2, characterized in that: In the step S2, the mass ratio of disodium ethylenediaminetetraacetate in the disodium ethylenediaminetetraacetate solution to the mass ratio of the powdered peanut shells is 2% to 8%.

5. The method for preparing a hard carbon sodium negative electrode material using peanut shell as raw material according to claim 2, characterized in that: In the step S3, the temperature of calcination and carbonization in the nitrogen atmosphere is 1200-1400° C., and the calcination and carbonization treatment time is 0.5-5 h.

6. A method for preparing a hard carbon sodium negative electrode material using peanut shell as raw material as claimed in claim 1, characterized in that: The method comprises the steps of: S0, placing peanut shells in a hydrochloric acid solution and heating the peanut shells, and then separating the solid matter from the solution, washing the solid matter and drying the solid matter; S1. The peanut shells dried in step S0 are placed in an air atmosphere for heating and pre-oxidation; S2. The pre-oxidized peanut shells are ground or crushed into powder, and a disodium ethylenediaminetetraacetic acid solution is added, stirred evenly, and then dried; S3. The mixture dried in step S2 is placed in a nitrogen atmosphere for calcination and carbonization, and after cooling, a hard carbon sodium negative electrode material using peanut shells as raw materials is obtained.

7. The method for preparing hard carbon sodium negative electrode material using peanut shell as raw material according to claim 6, characterized in that: In the step S0, the concentration of the hydrochloric acid is 0.5 to 2 mol / L, the heating temperature is 60 to 150° C., and the heating time is 0.5 to 5 h.

8. The method for preparing hard carbon sodium negative electrode material using peanut shell as raw material according to claim 6, characterized in that: In the step S1, the pre-oxidation temperature is 200-300°C.

9. The method for preparing hard carbon sodium negative electrode material using peanut shell as raw material according to claim 6, characterized in that: In the step S2, the mass ratio of disodium ethylenediaminetetraacetate in the disodium ethylenediaminetetraacetate solution to the mass ratio of the powdered peanut shells is 2% to 8%.

10. The method for preparing hard carbon sodium negative electrode material using peanut shell as raw material according to claim 6, characterized in that: In the step S3, the temperature of calcination and carbonization in the nitrogen atmosphere is 1200-1400° C., and the calcination and carbonization treatment time is 0.5-5 h.

Citation Information

Patent Citations

  • Preparation method of element modified soft and hard composite carbon sodium battery negative electrode material

    CN116741962A

  • Preparation method of high-capacity asphalt-based hard carbon sodium ion battery negative electrode material

    CN116969442A

  • Phosphorus-nitrogen co-doped coal-based hard carbon composite negative electrode material and preparation method thereof

    CN117673315A

  • Preparation method and application of biomass carbon negative electrode material of sodium-ion battery

    CN118083953A

  • Sodium Ion Battery Cathode Material, and a Preparation Method and Application therefor

    US20240400408A1

Cited By

  • Biomass-based sodium-ion battery hard carbon materials, their preparation methods and applications

    CN120664526B

  • Sodium-ion battery hard carbon negative electrode material and preparation method and application thereof

    CN120964770A